Factors predicting the presence of small bowel lesions in patients with obscure gastrointestinal bleeding. Issue 4 (17th December 2012) - Sakai, Eiji; Endo, Hiroki; Taniguchi, Leo; Hata, Yasuo; Ezuka, Akiko; Nagase, Hajime; Yamada, Eiji; Ohkubo, Hidenori; Higurashi, Takuma; Sekino, Yusuke; Koide, Tomoko; Iida, Hiroshi; et al.
Abstract : Aim: To identify the predictive factors for the presence of small bowel lesions in patients with obscure gastrointestinal bleeding (OGIB). Methods: A total of 242 patients with OGIB (overt 149: occult 93) were retrospectively included in the present study. Capsule endoscopy (CE) was carried out to investigate the small bowel, and detected lesions were classified according to the P0‐P2 system. Only P2 lesions were defined as significant lesions. Univariate and multivariate logistic regression analyses were carried out to define the predictive factors for the presence of small bowel lesions. Results: In patients with overt OGIB, chronic kidney disease (CKD) ≥stage 4 (odds ratio [OR] 4.03; 95% confidence interval [CI] 1.45–11.1, P = 0.007) was identified as an independent predictor of the presence of vascular lesions, and a history of non‐steroidalanti‐inflammatory drug (NSAID) use as that of erosive/ulcerated lesions (OR 4.73; 95% CI 1.47–15.2, P = 0.009). However, in patients with occult OGIB, no significant predictors of the presence of vascular lesions were identified, whereas a history of low‐dose aspirin (LDA) (OR 3.57; 95% CI 1.21–10.5, P = 0.02) and proton pump inhibitor (PPI) use (OR 3.18; 95% CI 1.02–9.92, P = 0.05) were identified as independent predictors of the presence of erosive/ulcerated lesions. Conclusions: Our results indicated that bleeding pattern and clinical characteristics could contribute to predicting the origin of OGIB.